Alternative Measures of Well-Being - Boarini, Romina (OECD Social, Employment and Migration Working Papers, 2006)
All discussions about the desirability of policy reforms rest on judgements about their effects on individuals and societal well-being. Yet, suitable measures for assessing how well-being is changing over time or compares across countries are lacking. This problem is, of course, not new and standard economic theory has provided, over the years, a range of insights about the criteria and domains that are most critical for the measurement of well-being, and on the relation between well-being and measures of economic resources. This paper does not revisit this theoretical discussion, nor does it provide a comprehensive review of different approaches to the measurement of well-being. It rather assesses whether GDP per capita is an adequate proxy as a measure of well-being or whether other indicators - used either as substitutes or as complements to GDP per capita - are more suitable for that purpose. Attention is limited to only some of the factors that influence well-being, and excludes some critical elements such as the environment, home production and other non-market factors